Description of grains hydration kinetics and its enhancement using the ultrasound technology - Pastor, Alberto Claudio Miano (2015)
The present work had as objective to study the hydration process of grains and its possible enhancement using the ultrasound technology. For that, it was studied the hydration kinetics of different grains (Andean lupin, Adzuki beans, sorghum grains and corn kernels) correlating the morphology with mathematical models and the mass transfer mechanisms. Moreover, the effect of the soaking water temperature and the grain initial moisture content were studied to complement the description of this process. The ultrasound application was studied for improving the hydration process, describing the possible mechanisms (direct and indirect effects) that improve the mass transfer process. Therefore, it was established the way by how water enters in the studied grains, demonstrating that the water transfer into the grains is a complex phenomenon and takes place not only due to diffusional mechanisms, but also by capillarity. In addition, suitable mathematical models were proposed and used to explain the processes, describing their parameters according to the grains morphology and the mass transfer mechanisms. Further, it was determined how ultrasound enhances the mass transfer and in which conditions the direct (inertial flow and sponge effect) and the indirect effects (micro channels formation by acoustic cavitation) take place in the process, maximizing the effect of this technology. Finally, it was demonstrated that the ultrasound technology enhanced the hydration process for corn kernels, reducing significantly the process time in approximately 35 %, without modifying the thermal, structural and rheological properties of their starch. In conclusion, the present work improved the description of the grain hydration phenomenon and proved that the ultrasound technology can be used to enhance this process without changing its main industrial component. It is highlighted that the obtained results are thus high desirable for both the industrial and academic point of view.